School Motivation Questionnaire for the Portuguese Population: Structure and Psychometric Studies. - Gomes Cordeiro, Pedro Miguel (2014)
It is presented the structure and psychometric studies of the “School Motivation Questionnaire”. The SMQ is a self-report questionnaire with 101 items, organized in sixteen scales that measure the students´ goal orientations, the perceived classroom goal structures, the perceived teacher’s autonomy support and the use of learning strategies. Twelve scales are adapted from the “Learning Climate Questionnaire”, “Perceptions of Instrumentality” and “Cuestionário a Estudiantes”. Four scales and five additional items are created new. The psychometric studies rely on a convenience sample consisting of 9th and 12th grade students ( = 485) of Portuguese schools. The factorial and construct validity, verified through several exploratory factorial analyses to the data, presents a final solution of six factors, labelled Strategies (F1), Teacher Extrinsic Goals (F2), Student Extrinsic Goals, Externally Regulated (F3) Teacher Intrinsic Goals (F4), Student Extrinsic Goals, Internally Regulated (F5), and Student Intrinsic Goals (F6). The six-factor solution explains a significant variance of the scale results (53.95%). Good coefficients of internal consistency are obtained for all factors, never below (.858; F6). In sum there is strong evidence to support the multi-dimensionality of SMQ, upholding that the data obtained is exploratory and applies for future validation studies.